Recent advancements in the hormonal stimulation of ovulation in swine - Knox RV (Dove Medical Press, 2015)
Robert V Knox Department of Animal Sciences, 360 Animal Sciences Laboratory, University of Illinois, Champaign Urbana, IL, USA Abstract: Induction of ovulation for controlled breeding is available for use around the world, and conditions for practical application appear promising. Many of the hormones available, such as human chorionic gonadotropin (hCG), gonadotropin-releasing hormone (GnRH) and its analogs, as well as porcine luteinizing hormone (pLH), have been shown to be effective for advancing or synchronizing ovulation in gilts and weaned sows. Each of the hormones has unique attributes with respect to the physiology of its actions, how it is administered, its efficacy, and approval for use. The timing for induction of ovulation during the follicle phase is critical as follicle maturity changes over time, and the success of the response is determined by the stage of follicle development. Female fertility is also a primary factor affecting the success of ovulation induction and fixed time insemination protocols. Approximately 80%–90% of female pigs will develop mature follicles following weaning in sows and synchronization of estrus in gilts. However, those gilts and sows with follicles that are less developed and mature, or those that develop with abnormalities, will not respond to an ovulatory surge of LH. To address this problem, some protocols induce follicle development in all females, which can improve the overall reliability of the ovulation response. Control of ovulation is practical for use with fixed time artificial insemination and should prove highly advantageous for low-dose and single-service artificial insemination and for use with frozen-thawed and sex-sorted sperm. Keywords: artificial insemination, follicle, hormone, ovulation, swine